Status Terkini Kondisi Ekosistem Terumbu Karang di Pulau Saobi dan Pulau Sapapan, Kepulauan Kangean, Sumenep - Handoko, Ahmad; Saptarini, Dian; Irawan, Dedi (Universitas Trunojoyo Madura, 2025)
Coral reefs are marine biota that have a fairly high level of sensitivity to changes in water conditions, both in terms of physical and chemical aspects. Damage experienced by coral reef ecosystems is increasingly occurring, this can be caused by human and natural activities. This research aims to determine the condition of the coral reef ecosystem on Saobi Island and Sapapan Island. The method used in this research is Underwater Photo Transect (UPT). The observation location consists of 7 stations, of which 4 stations are on Saobi Island and 3 stations are on Sapapan Island. The growth forms found are Acropora Branching (ACB), Acropora Digitate (ACD), Acropora Submassive (ACS), Acropora Tabulate (ACT), Coral Branching (CB), Coral Encrusting (CE), Coral Foliose (CF), Coral Massive (CM), Coral Mushroom (CMR), Coral Submassive (CS). The condition of the coral on Sapapan Island is included in the good category at station 1 with a live coral cover percentage of 53.67% and in the very good category at station 2 and station 3 with a live coral cover percentage of 78.87% and 77.80%. Meanwhile, on Saobi Island, the condition of coral reefs at station 1 is included in the medium category with a percent cover value of 46.53% and station 2 is 67.53%, station 3 is 65.33% and station 4 is 52.47% which is included in good category.